Women Writers in Australia and North America: Bearing Witness to the Hellenic Immigration Experience - Georgoudaki, Ekaterini (Études helléniques / Hellenic Studies, 2005)
Through language women poets and fiction writers of Greek and Greek-Cypriot origin recreate their own and other people's experiences of expatriation and settlement in Australia, Canada and the USA. Using a variety of characters they present migrants' dreams, first impressions and difficulties in adjusting to a different cultural and linguistic environment. Also revealed are the racism enountered and the struggle for survival in the host country's highly competitive, class-structured capitalist Society. The writers also relate their impression of the morherland when they return after many years of absence. The discussion of the texts highlights the literary, historical and socio-political importance of women writers of Greek and Greek-Cypriot origin and their experience.